Why Did Poverty Decline in India? : A Nonparametric Decomposition Exercise - Balcazar, Carlos Felipe; Desai, Sonal; Murgai, Rinku; Narayan, Ambar (World Bank, Washington, DC, 2016)
This paper uses panel data to analyze factors that contributed to the rapid decline in poverty in India between 2005 and 2012. The analysis employs a nonparametric decomposition method that measures the relative contributions of different components of household livelihoods to observed changes in poverty. The results show that poverty decline is associated with a significant increase in labor earnings, explained in turn by a steep rise in wages for unskilled labor, and diversification from farm to nonfarm sources of income in rural areas. Transfers, in the form of remittances and social programs, have contributed but are not the primary drivers of poverty decline over this period. The pattern of changes is consistent with processes associated with structural transformation, which add up to a highly pro-poor pattern of income growth over the initial distribution of income and consumption. However, certain social groups (Adivasis and Dalits) are found to be more likely to stay in or fall into poverty and less likely to move out of poverty. And even as poverty has reduced dramatically, the share of vulnerable population has not.